2000
DOI: 10.1099/00221287-146-9-2175
|View full text |Cite
|
Sign up to set email alerts
|

ISBst12, a novel type of insertion-sequence element causing loss of S-layer-gene expression in Bacillus stearothermophilus ATCC 12980 The GenBank accession number for the sequence reported in this paper is AF162268.

Abstract: The cell surface of the surface layer (S-layer)-carrying strain of Bacillus stearothermophilus ATCC 12980 is completely covered with an oblique lattice composed of the S-layer protein SbsC. In the S-layer-deficient strain, the S-layer gene sbsC was still present but was interrupted by a novel type of insertion sequence (IS) element designated ISBst12. motifs were identified at the N-terminal part of the putative transposase. As revealed by Southern blotting, ISBst12 was present in multiple copies in the Slayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…PCR analysis revealed that the coding region of the sbsC gene was interrupted by a new type of IS element designated ISBst12, which currently cannot be attributed to any of the known IS families. Southern hybridization showed that ISBst12 was present in multiple copies in the S-layer-carrying strain, as well as in that with the S-layer-deficient phenotype (34). Interestingly, ISBst12 was also detected in B. stearothermophilus PV72/p6, its oxygen-induced strain variant PV72/p2, and the strain with the S-layer-deficient phenotype (PV72/T5).…”
Section: S-layer-deficient Phenotypes and S-layer Variationmentioning
confidence: 85%
“…PCR analysis revealed that the coding region of the sbsC gene was interrupted by a new type of IS element designated ISBst12, which currently cannot be attributed to any of the known IS families. Southern hybridization showed that ISBst12 was present in multiple copies in the S-layer-carrying strain, as well as in that with the S-layer-deficient phenotype (34). Interestingly, ISBst12 was also detected in B. stearothermophilus PV72/p6, its oxygen-induced strain variant PV72/p2, and the strain with the S-layer-deficient phenotype (PV72/T5).…”
Section: S-layer-deficient Phenotypes and S-layer Variationmentioning
confidence: 85%
“…In G. stearothermophilus strain variants, expression of a completely new type of S‐layer protein is accompanied by synthesis of a different type of SCWP and S‐layer variation may also lead to a change in the lattice type (Sára et al , 1994, 1996). Regarding the development of S‐layer‐deficient strain variants, the importance of insertion sequence (IS) elements has been demonstrated for various organisms (Egelseer et al , 2000; Scholz et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A second group of closely related IS, widely spread among both bacteria and Archaea are thought to represent a subgroup within the IS66 family (194). The founder member, ISBst12, originally isolated from Bacillus stearothermophilus, was described as a novel family (195), but identification of many additional examples suggests that the ISBst12 and IS66 groups should be considered a single family. ISBst12 are found in Actinobacteria, Cyanobacteria, Deinococcus/Thermus, Firmicutes, and Planctomycetes as well as in Proteobacteria.…”
Section: Is66 (I) Generalmentioning
confidence: 99%